A case report and literature review of primary distal renal tubular acidosis resulting from a mutation in ATP6V0A4 - Chang, Chenyang; Chen, Hao; Wang, Min; Chen, Jingshan; Zou, Yaomin; Hu, Shaowen; Luo, Kaiyuan; Rao, Xingyu; Zhu, Huifang (Frontiers in Pediatrics, 2025)
Primary renal tubular acidosis is an inherited disorder with heterogeneous clinical presentations, including chronic metabolic acidosis, electrolyte imbalances (e.g., hypokalemia), skeletal abnormalities, and urinary tract symptoms. We report a noteworthy case of a 7-month-old infant who presented with recurrent vomiting and hypokalemia. Laboratory investigations confirmed hypokalemia, metabolic acidosis with hyperchloremia, and inappropriately alkaline urine, leading to a strong suspicion of primary renal tubular acidosis. Genetic analysis by whole-exome sequencing identified a novel homozygous missense mutation (c.1418C > T) in the ATP6V0A4 gene on chromosome 7 in the proband. This specific variant is exceptionally rare and is associated with a severe, atypical phenotype manifesting in early infancy. This case expands the known mutational and phenotypic spectrum of ATP6V0A4-related renal tubular acidosis. Our findings aim to enhance the understanding of this disease by correlating the clinical course with its genetic etiology, thereby establishing a molecular basis for precise etiological diagnosis, informed genetic counseling, and prenatal diagnosis.